Development of a strategic plan for wood charcoal exportation from the Carbonera Buenos Aires company, Oratorio, Santa Rosa, Guatemala - Molina A., Ernesto (Zamorano: Escuela Agrícola Panamericana, 2025)
Carbonera Buenos Aires began producing wood charcoal in 2021 in Oratorio, Santa Rosa, Guatema-la, targeting the "La Terminal" retail market in Guatemala City. The company saw a market oppor-tunity in wood charcoal and now sells 9.09 tons weekly at competitive prices. The raw material, Guatemalan Oak, is sourced from Jutiapa and Santa Rosa. The company's strategic location, good roads, and sufficient area for expansion support its operations. Using handmade ovens and a workforce of five, the charcoal production process takes one week, ensuring high quality. CEO Jorge Molina is exploring export opportunities for higher profit margins despite a strong local mar-ket presence. A market study identified the USA as a viable export market due to favorable logis-tics and profitability. Although the company currently has no US clients, a scenario was developed assuming a standard export price and considering key variables like export price and local produc-tion. The project compared the financial viability of local sales versus exports using financial indica-tors such as Net Present Value (NPV) and Internal Rate of Return (IRR). The analysis showed better financial outcomes for exporting. Additionally, risk software @risk was used to estimate the prob-ability of achieving the projected financial indicators. The results indicated a 72.2% probability of higher profits from exporting over a 10-year projection, based on 50,000 possible scenarios. This (Indexbox, 12/27/2022)suggests that expanding into the export market is a favorable option for Carbonera Buenos Aires.